143 Long-term cardiac and vascular phenotype of young women with pregnancies complicated by preeclampsia. (16th May 2012) - Lazdam, M; de la Horra, A; Diesch, J; Francis, J; Kenworthy, Y; Shore, A; Redman, C; Neubauer, S; Kharbanda, R; Alp, N; Kelly, B; Leeson, P
Abstract : Background: Preeclampsia is an independent risk factor for cardiovascular disease and is associated with a range of maternal cardiovascular abnormalities during the perinatal period. We studied mothers late after preeclampsia to define persistent cardiac and vascular changes that might link preeclampsia to later disease and identified key pregnancy factors that predicted the variation. Methods: 140 women aged 28–50 years were studied 6–13 years after the index pregnancy. 90 had preeclampsia (45 early onset before 34 weeks gestation and 45 later onset) and 50 had normotensive uncomplicated pregnancies. Women with cardiovascular risk factors before pregnancy were excluded. Central blood pressure (BP) and arterial stiffness (pulse wave velocity (PWV)/augmentation index (AI)) were assessed by applanation tonometry, common carotid intima media thickness (cIMT) by ultrasound, cutaneous capillary density by intravital microscopy and endothelial function by flow mediated dilatation (FMD). 46 women returned for assessment of cardiac structure and function by magnetic resonance and echocardiography as well as ambulatory blood pressure monitoring. Fasting lipids, glucose, insulin and circulating cytokines and adhesion molecules were measured in all subjects. Results: Women with a previous history of preeclampsia had 4–12 mm Hg higher peripheral and central BP (p<0.001) as well as characteristic differences in ambulatory measures. They also had increased arterial stiffness (ANOVA p=0.04), cIMT (ANOVA p=0.006) and capillary rarefaction (ANOVA p=0.005). Cardiac size and systolic function were preserved but there was evidence of abnormal diastolic relaxation (E/E' – ANOVA p=0.04) and elevated total: HDL cholesterol (p=0.003), insulin resistance (p=0.04), circulating TNFα (p=0.007) and eSelectin (p<0.001). All changes were graded according to the timing and severity of preeclampsia. Conclusion: Structural micro and macrovascular changes predominate in young women a decade after preeclampsia. Alterations in metabolic markers and mild changes in diastology are also evident. Timing and severity of preeclampsia are predictive of these differences and may identify women at greatest potential benefit from primary prevention advice.